Variable-valence ion and heterointerface accelerated electron transfer kinetics of electrochemical water splitting. Issue 23 (18th February 2022) - Lu, Mengfei; Kong, Shaoxi; Yan, Shicheng; Zhou, Peng; Yu, Tao; Zou, Zhigang
Abstract : The electron transfer from OER intermediates via the amorphous NiFeOOH shell was efficiently accelerated by the variable-valence V 3+/4+ acceptor at core@shell interface and the heterojunction effect in Ni3 Fe1− x V x /Ni3 Fe1− x V x N core, significantly facilitating the OER performance. Abstract : Accelerating electron transfer kinetics is an efficient strategy to tackle the sluggish oxygen evolution reaction (OER). Herein, Ni3 Fe1− x V x /Ni3 Fe1− x V x N heterojunctions were elaborately constructed to demonstrate that the coupling of variable-valence metal doping and nanoalloy/nitride heterointerfaces could optimize the OER performance of antiperovskite nitrides. The spectroscopic results suggested that during OER electrochemical surface reconstruction occurred to form an assembly of a crystalline Ni3 Fe1− x V x /Ni3 Fe1− x V x N heterojunction core and amorphous NiFeOOH shell (Ni3 Fe1− x V x /Ni3 Fe1− x V x N@NiFeOOH). The electron transfer from the OER intermediates via the amorphous NiFeOOH shell was efficiently accelerated by the variable-valence V 3+/4+ electron acceptor at the core@shell interface and the heterojunction effect in the Ni3 Fe1− x V x /Ni3 Fe1− x V x N core. As a result, the oxygen and hydrogen evolution reactions can occur at low overpotentials of 260 mV at 50 mA cm −2 and 113 mV at 10 mA cm −2, respectively, affording a low cell voltage of 1.66 V at 10 mA cm −2 for water splitting in alkaline electrolyte (1.0 M KOH). Our results provide a new attempt at improving water splitting kinetics via the variable-valence ion coupling heterojunction effect.